Fair, equal, safe, and universal eqipment in parasports: Experiences from development of a sit-ski and lower-leg prosthesis for cross-country skiing - Danvind, J.; Ohlsson, M.; Skoglund, P. (Science and Skiing VII, 2018)
Sports and recreational equipment for people with a disability is a prerequisite for health and inclusion through physical activity, sports, and outdoor activities. The accessibility and universality of equipment are very low on the global level and, when it comes to youth and their equipment needs, it is even worse. Based on experiences from the fourth ASEAN Para Games, Wong (2008) highlights the high cost of sporting equipment as a crucial factor that is widening the gap between countries in the Paralympic family at the elite level and hindering beginners in parasports. Although this is a societal challenge, Wong (2008) does not ask to limit technical and performance enhancement through equipment control, but instead to level out differences in accessibility by universal low-cost equipment. Product development in general plays a central role in the development of today's society. Most products are a result of the market drivers and the interplay between demand and supply. In equipment development for parasports, the market drivers for development are not strong enough to provide equipment for all. Also, the demands from athletes, coaches, manufacturers, and sport organizations are not in balance for a sustainable development (i.e., access to the equipment should be fair, equal, safe, and universal) (IPC, 2011). The imbalance in demands for new sporting equipment and new sport technology from different parties has historically led to controversies (Dyer, 2015). In this work, the imbalance in equipment development for parasports is discussed. The objective of this work is to provide the engineering society with an understanding of factors influencing the equipment development for parasports—an understanding that hopefully will shorten the equipment development process, minimize the number of technology disputes, and increase universal equipment development for all. Because this work was limited to Paralympic sports from grassroots to elite levels and the evaluation of the two pieces of equipment were limited to the authors` experiences, this work is more of an opinion piece than a scientific paper.